Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Compute the below sum:


My working:

$\sum_{i=1}^{n}\sum_{j=1}^{n}ij = \sum_{i=1}^{n}i\frac{n(n+1)}{2}$

Now since $\frac{n(n+2)}{2}$ is just a constant we can take it out of the sum

$\sum_{i=1}^{n}i\frac{n(n+1)}{2} = \frac{n(n+1)}{2}\sum_{i=1}^{n}i$

$\sum_{i=1}^{n}i\frac{n(n+1)}{2} = \frac{n(n+1)}{2}\times\frac{n(n+1)}{2}$

So we get:

$\sum_{i=1}^{n}\sum_{j=1}^{n}ij = (\frac{n(n+1)}{2})^2$

I am not sure if this is correct, or if I am using the properties of Series correctly.

share|cite|improve this question
You are correct. One way to check is to do a few examples - n=1,2,3. – Thomas Andrews Apr 29 '13 at 12:53
Generally correct; in your first line I would pull the $i$ out of the inner sum to justify replacing it with $\frac{n(n+1)}{2}$. – vadim123 Apr 29 '13 at 12:53
incidentally $\sum_{i=1}^n\sum_{j=1}^n ij = (\sum_{i=1}^ni)(\sum_{j=1}^nj)$ – Gautam Shenoy Apr 29 '13 at 12:59
up vote 4 down vote accepted

another way: $\sum_{i=1}^{n}\sum_{j=1}^{n}ij=\sum_{i=1}^{n}i * \sum_{j=1}^{n}j=\frac{n(n+1)}{2} * \frac{n(n+1)}{2}$

share|cite|improve this answer

Your proof is correct.

Since $n(1+2+3+\ldots+n-1)n+n(1+2+3+\ldots+n-1)+n^2=n^3$ using induction it is not hard to show that $\sum_{i=1}^n\sum_{j=1}^nij=\sum_{k=1}^nk^3$.
Therefore you also have $\sum_{k=1}^nk^3=\left(\dfrac{n(n+1)}{2}\right)^2$. Of course if you know the last identity you can use it for a different proof of your result.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.